2016
DOI: 10.1002/stem.2490
|View full text |Cite
|
Sign up to set email alerts
|

H/ACA Box Small Nucleolar RNA 7A Promotes the Self-Renewal of Human Umbilical Cord Mesenchymal Stem Cells

Abstract: Human umbilical cord blood derived mesenchymal stem cells (uMSC) are pluripotent cells that have been now considered as a promising candidate for various cell-based therapies. However, their limited in vitro proliferation ability and the gradual loss of pluripotency set barricades for further usages. Emerging evidence suggests that small nucleolar RNAs (snoRNA) are actively involved in cell proliferation especially in tumor cells, but their roles in stem cells are largely unknown. In this study, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Among these paralogues, SNORA7B and SNORA7A are over 98% identical and target the same 28S rRNA pseudouridylation sites [30, 31]. Zhang et al [32] demonstrated that both SNORA7B and SNORA7A could promote the self-renewal of human umbilical cord blood-derived mesenchymal stem cells (uMSCs). The SNORA7B gene is located on chromosome 3q21 as an intron in the RPL32P3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Among these paralogues, SNORA7B and SNORA7A are over 98% identical and target the same 28S rRNA pseudouridylation sites [30, 31]. Zhang et al [32] demonstrated that both SNORA7B and SNORA7A could promote the self-renewal of human umbilical cord blood-derived mesenchymal stem cells (uMSCs). The SNORA7B gene is located on chromosome 3q21 as an intron in the RPL32P3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of PWS locus orphan snoRNAs remains to be determined. New and unexpected roles have been ascribed to several canonical and orphan snoRNAs in recent years ( 27 , 48 52 and reviewed in 53 ), straitening our convictions that this class of non-coding RNAs is more than a simple regulator of rRNA decoration.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the top most down-regulated genes by BDE-47 included glutamic-oxaloacetic transaminase 1 (Got1), which is important for amino acid metabolism and the urea and tricarboxylic acid cycles [ 122 ]; Sestrin 2 (Sesn2) and dopachrome tautomerase (Dct), both of which protect cells from oxidative stress [ 123 , 124 ]; ephrin type-A receptor A2 (Epha2), which mediates neural development [ 125 ]; and small nucleolar RNA 7A (Snora7a). Snora7a has been reported to promote cell proliferation and suppress differentiation in mesenchymal stem cell [ 126 ]. These results suggested that without the presence of gut microbiome, not only steroid and bile acid signaling pathways, but the cellular signaling were distinctly regulated by BDE-47 in GF mice.…”
Section: Resultsmentioning
confidence: 99%